A Study of Cooperative Learning Model with Process Skills in Elementary School - Kamid, Kamid; Syaiful, Syaiful; Theis, Roseli; Sufri, Sufri; Rohana, Siti (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2022)
The purpose of this study was to determine student responses to process skills on jigsaw and STAD learning models for mathematics subjects. This research was conducted at SD Negeri 04/I Sungai Ruan Ilir and SD Negeri 52/I Kilangan II in Batanghari district. The method in this research is comparative quantitative data analysis, where comparative is research that compares two or more variables. The result of this research is that there is a hypothesis test result (T) which shows that there are differences in the jigsaw learning model at SD Negeri 04/I Sungai Ruan Ilir and SD Negeri 52/I Kilangan II in Batanghari district on Mathematics. Furthermore, it was found that there were differences in the learning model of student team achievement divisions (STAD) at SD Negeri 04/I Sungai Ruan Ilir and SD Negeri 52/I Kilangan II in Batanghari district regarding Mathematics. So it can be concluded that there is a comparison between 2 elementary schools on process skills in the jigsaw and STAD learning models on mathematics subjects